The effectiveness of the Culturally Responsive Transformative Teaching (CRTT) model assisted by podcast and e-assessment on students’ scientific literacy and communication skills - Kurnia Marta Indi Fahira; Sri Yamtinah; Antuni Wiyarsi; Hayuni Retno Widarti; Ari Syahidul Shidiq (Education and Development Research, 2026)
This study aimed investigated the effectiveness of the Culturally Responsive Transformative Teaching (CRTT) model supported by podcasts and e-assessment in improving students’ scientific literacy and communication skills on chemical reactions topics. A quasi-experimental non-equivalent control group pretest–posttest design was employed. The participants consisted of 72 tenth-grade students selected through cluster random sampling from a public senior high school in Boyolali, Indonesia, who were assigned to either a to an experimental class (CRTT supported by podcast and e-assessment) or a control class (conventional instruction). Scientific literacy was measured using a 15-item multiple-choice test, while communication skill was assessed using a 12-item observation sheet based on four-point Likert scale. Since the data did not meet parametric assumptions, non- Mann–Whitney U and Kruskal–Wallis tests were used for analysis. The result showed that the experimental class achieved higher posttest score in scientific literacy 84 than the control class (75), with a statically significant difference (p<0.001). Similarly, the experimental class obtained a higher mean score for communication skills (41.1) than the control class (31.9), with a significant difference (p=0.001). This study lies in the integration of CRTT, culturally grounded podcast and e-assessment within chemistry instruction to simultaneously enhance students’ scientific literacy and communication skills. Culturally responsive pedagogy supported by digital learning resources and e-assessment tools can serve as an effective strategy for improving students’ understanding and communication of abstract chemistry concepts, particularly those related to s chemical reactions.